Recurrent multi-drug-resistant tuberculosis with unilateral destroyed lung in pregnancy: a case report - Irene Sinta Febriana; Sayugo Atikah; Sri Pudyastuti (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran)
Background: Multi-drug-resistant Tuberculosis (MDR-TB) remains a public health problem in developing countries such as Indonesia. The extensive parenchymal damage due to MDR-TB could manifest as an irreversible destroyed lung, leading to respiratory and also cardiovascular complication. Its occurrence in pregnancy is uncommon but is highly associated with higher mortality and morbidity for both maternal and fetal.Case Report: We report a case of 24 year old primigravida in National Respiratory Center Hospital, diagnosed with an unilateral destroyed lung due to MDR-TB in pregnancy at 32 weeks of gestational age. On initial presentation, she reported fatigue, nausea, night sweats, chronic dyspnoe and was found to have complete left destroyed lung. Her disease was managed during pregnancy using long-term oxygen therapy despite persistent desaturation.Conlusion: Aside from frequent monitoring, prolonged oxygen therapy might benefit the chronic hypoxia condition in gestational destroyed lung due to previous MDR-TB infection, for preventing maternal-fetal mortality and morbidities, such as respiratory failure and IUGR.AbstrakLatar Belakang: Tuberkulosis Multi-drug-resistant (TB-MDR) tetap menjadi masalah kesehatan pada negara berkembang, seperti Indonesia. Kerusakan parenkin luas yang diakibatkan oleh infeksi TB-MDR dapat bermanifestasi sebagai kerusakan paru ireversibel, dengan komplikasi respiratorik dan kardiovaskular. Kejadian kerusakan paru akibat TB-MDR dalam kehamilan jarang terjadi, namun berdampak pada peningkatan mortalitas dan morbiditas pada janin dan ibu. Laporan Kasus: Studi ini melaporkan kasus perempuan primigravida 24 tahun didiagnosa dengan kerusakan paru unilateral akibat infeksi TB-MDR pada kehamilan 32 minggu di RS Pusat Paru Nasional. Pada pemeriksaan awal, didapatkan pasien mengeluhkan kelelahan kronik, nausea, keringat malam, sesak kronik dan didapatkan memiliki kerusakan paru kiri komplit. Keadaan pasien dalam kehamilan ditatalaksana dengan terapi oksigen jangka panjang untuk mengatasi desaturasi persisten Kesimpulan: Di samping pengawasan ketat, terapi oksigen jangka panjang dapat menjadi tatalaksana utama untuk kondisi hipoksia kronik pada kerusakan paru dalam kehamilan akibat infeksi lama TB-MDR untuk mencegah morbiditas dan mortalitas ibu dan janin, seperti gagal napas dan pertumbuhan janin terhambat (PJT).